Teaching Introductory Statistics with DataCamp. Issue 1 (2nd January 2020) - Baumer, Benjamin S.; Bray, Andrew P.; Çetinkaya-Rundel, Mine; Hardin, Johanna S.
Abstract: We designed a sequence of courses for the DataCamp online learning platform that approximates the content of a typical introductory statistics course. We discuss the design and implementation of these courses and illustrate how they can be successfully integrated into a brick-and-mortar class. We reflect on the process of creating content for online consumers, ruminate on the pedagogical considerations we faced, and describe an R package for statistical inference that became a by-product of this development process. We discuss the pros and cons of creating the course sequence and express our view that some aspects were particularly problematic. The issues raised should be relevant to nearly all statistics instructors. Supplementary materials for this article are available online.